Relation between experimental and non-experimental study designs. HB vaccines: a case study. Issue 1 (1st January 1999) - Jefferson, T; Demicheli, V
Abstract : STUDY OBJECTIVE: To examine the relation between experimental and non-experimental study design in vaccinology. DESIGN: Assessment of each study design's capability of testing four aspects of vaccine performance, namely immunogenicity (the capacity to stimulate the immune system), duration of immunity conferred, incidence and seriousness of side effects, and number of infections prevented by vaccination. SETTING: Experimental and non-experimental studies on hepatitis B (HB) vaccines in the Cochrane Vaccines Field Database. RESULTS: Experimental and non-experimental vaccine study designs are frequently complementary but some aspects of vaccine quality can only be assessed by one of the types of study. More work needs to be done on the relation between study quality and its significance in terms of effect size.